Endoscopic activity in asymptomatic patients with an ileal pouch is associated with an increased risk of pouchitis. Issue 11 (3rd October 2019) - Kayal, Maia; Plietz, Michael; Radcliffe, Marlana; Rizvi, Anam; Yzet, Clara; Tixier, Emily; Hirten, Robert P.; Cohen, Benjamin; Sylla, Patricia; Khaitov, Sergey; Greenstein, Alexander; Colombel, Jean‐Frederic; et al.
Summary: Background: The significance of endoscopic activity in asymptomatic ulcerative colitis (UC) patients with an ileal pouch is unknown. Aim: To investigate the association of endoscopic pouch activity in asymptomatic patients with the subsequent development of pouchitis. Methods: We analyzed a retrospective cohort of patients with UC or IBD‐unspecified who underwent a total proctocolectomy with ileal pouch anal anastomosis (IPAA). Asymptomatic patients with a Pouchitis Disease Activity Index (PDAI) symptom sub‐score of zero who underwent an index surveillance pouchoscopy were included. Endoscopic pouch body activity was graded as 0: normal, 1: mucosal inflammation, or 2: mucosal breaks (ulcers and/or erosions). The primary outcome was primary acute idiopathic pouchitis defined as PDAI score ≥ 7 with symptoms lasting less than four weeks and responsive to standard antibiotics, not otherwise meeting criteria for secondary pouchitis. The secondary outcome was chronic idiopathic pouchitis defined as PDAI score ≥ 7 with symptoms lasting greater than four weeks despite standard antibiotics. Predictors of pouchitis were analyzed using Kaplan‐Meier and Cox regression methods with hazard ratios (HR) and 95% confidence intervals (CI) reported. Results: 143 asymptomatic pouch patients were included. Index endoscopic pouch body activity was 0 in 86 (60.1%) patients, 1 in 26 (18.2%) and 2 in 31 (21.7%). The median length of follow‐up after index surveillance pouchoscopy was 3.03 [IQR 1.24‐4.60] years. Primary acute idiopathic pouchitis occurred in 44 (31%) patients and chronic idiopathic pouchitis in 12 (8.4%). Grade 2 endoscopic pouch activity was associated with the development of acute pouchitis (HR 2.39, 95% CI 1.23‐4.67), although not chronic pouchitis (HR 1.76, 95% CI 0.53‐5.87). Histologic inflammation in endoscopically normal pouch mucosa was not associated with acute or chronic pouchitis. Conclusions: Mucosal breaks are present in nearly a quarter of asymptomatic patients with IPAA and are associated with an increased risk of acute pouchitis. Abstract : LINKED CONTENT This article is linked to Townsend and Subramanian and and Yamamoto et al and Kayal and Ungaro papers. To view these articles, visit https://doi.org/10.1111/apt.15536 and https://doi.org/10.1111/apt.15544 and https://doi.org/10.1111/apt.15566 and https://doi.org/10.1111/apt.15582 .